VD_FINDINFO PPD 4/15 - 6/2016 vom 28. August 2014 - VD Tribunal cantonal (2014)
PRÉVOYANCE PROFESSIONNELLE, DIVORCE, PARTAGESENS GÉNÉRAL, INTÉRÊT MORATOIRE, INTÉRÊT RÉMUNÉRATOIRE | 122 CC, 22 LFLP, 7 OLP, 8a al. 1 OLP, 12 OPP2, 111 al. 1 LPA-VD